The value of science: Address by Professor Sir Peter Gluckman at the 2013 NZAS Conference, Wellington, 3 April 2013 - Gluckman, Peter (New Zealand Science Review, 2013)
​The key issue for today’s meeting is that of the perceived value of public funding of science to both society and the taxpayer. Addressing this is a perennial challenge, and one in which the science community has to do better in advancing the case. For, in the end, policy formation is strongly inﬂuenced by political dynamics and public opinion, and investing more in science must be seen to have beneﬁts that politicians can own. In many other countries the science community has done a much better job in enjoining other parts of the community to be advocates for science. Too often, and not without justiﬁcation, the public perception of science advocacy by scientists is one of self-serv-ing promotion of a narrow piece of research, or of a fabrication based on naïve economic arguments. If science is genuinely for the public good, scientists need to engage the public in the arguments for it. The case is made more problematic when scientists confuse knowledge brokerage with advocacy – both are proper roles, but public trust in science requires clarity as to what role individuals are playing. Such confusion has raised cynicism in policy circles and in the media, yet the issue of the value of science to the taxpayer is both recognisably logical on one hand and has a deep values-based component on the other.